Selection of molecular markers for genetic certification of Triticum aestivum - M. A. Samarina; D. S. Uliyanov; T. D. Mokhov; Ya. S. Meglitskaya; P. Yu. Krupin; G. I. Karlov; P. N. Kharchenko; S. I. Voronov; N. V. Davydova; M. G. Divashuk (Зерновое хозяйство России)
According to the Law “On Seed Production”, all varieties or hybrids included in the state register shall be provided for genetic passports, as well as making a list of plants’ species, the production of which is aimed at ensuring food security. However, the use of morphological characteristics does not allow distinguishing genetically similar samples, identifying hidden genetic variability and ensuring control of the homogeneity of the initial material. In connection with these limitations, the purpose of the current work was to develop approaches for the selection of molecular genetic mic- rosatellite markers (SSR markers) to differentiate common wheat varieties. In accordance with the purpose, there has been conducted a literature review regarding methods for genetic certification and evaluation of the diversity of spring common wheat based on polymorphism of microsatellite loci, and there has been generated a set of Triticum aestivum genome assemblies from the NCBI Gen Bank. Based on the literature data, there have been selected the most polymorphic SSR markers using the invented algorithm. The analysis of databases of SSR markers in the genome of common wheat using bioinformatics methods allowed establishing a minimal discriminatory set of 20 markers that can detect 419 different alleles in Triticum aestivum. The results obtained can become the necessary theoretical foundation for further practical research.